Carrier risk status changes resulting from mutation testing in hereditary non-polyposis colorectal cancer and hereditary breast-ovarian cancer. Issue 8 (14th August 2003) - Watson, P; Narod, S A; Fodde, R; Wagner, A; Lynch, J F; Tinley, S T; Snyder, C L; Coronel, S A; Riley, B; Kinarsky, Y; Lynch, H T
Abstract : Context : In hereditary cancer syndrome families with an identified cancer associated mutation, mutation testing changes the carrier risk status of the tested person and may change the carrier risk status of relatives. Objective : This study aimed to describe the change in the distribution of carrier risk status resulting from testing in hereditary breast-ovarian cancer (HBOC) and hereditary non-polyposis colorectal cancer (HNPCC) families. Design : This was an observational cohort study. Patients : The cohort included members of 75 HBOC and 47 HNPCC families. Of the 10 910 cohort members, 1408 were tested for a mutation and learned their test results. Outcome measure : Carrier risk for all cohort members was assessed before and after mutation testing. Results : There was a change in carrier risk status in 2906 subjects after testing of 1408 family members. The most common type of carrier risk change, from at risk to non-carrier status, accounted for 77% of the risk changes; 12% were a change to known carrier status from a lower risk. Sixty percent of persons with a carrier risk status change were not themselves tested; their risk status changed because of a relative's test result. Conclusions : Carrier risk status changes from uncertainty to certainty (that is, to carrier or to non-carrier) account for 89% of risk changes resulting from testing. These risk changes affect cancer prevention recommendations, most commonly reducing their burden. Current practices do not ensure that untested family members are informed about changes in their carrier risk status which result from mutation testing of their relatives.